2018
DOI: 10.48550/arxiv.1810.13390
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unexpected Zero Bias Conductance Peak on the Topological Semimetal Sb(111) with a Broken Bilayer

Abstract: The long-sought Majorana fermion is expected to manifest in a topological-superconductor heterostructure as a zero bias conductance peak (ZBCP). As one promising platform for such heterostructures, we investigate the cleaved surface of the topological semimetal Sb(111) using scanning tunneling microscopy and spectroscopy. Remarkably, we find a robust ZBCP on some terraces of the cleaved surface, although no superconductor is present. Using quasiparticle interference imaging, Landau level spectroscopy and densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…We observe bi-atomiclayer steps of the height 4.0 Å, as shown in Fig. 4(a), consistent with previous reports [17][18][19]. We acquire z(V ) spectra at each point on a line [inset of Fig.…”
supporting
confidence: 87%
“…We observe bi-atomiclayer steps of the height 4.0 Å, as shown in Fig. 4(a), consistent with previous reports [17][18][19]. We acquire z(V ) spectra at each point on a line [inset of Fig.…”
supporting
confidence: 87%
“…35,54 The possibility of such errors arising in the interpretation of zero-bias anomalies have also been discussed in the context of other topological materials. 34 Using our exact analytical expressions, we show that the bound state wavefunctions for point defects in two dimensions decay monotonously as an inverse-square power law at large distances, without showing any Friedel-like oscillations. On the other hand, in the normal gap regime, the power-law states give way to conventional exponentially localized states upon the loss of superconducting order, which are qualitatively similar to subgap states in disordered semiconductors.…”
Section: Discussionmentioning
confidence: 88%
“…Indeed, such features may appear in point-contact spectroscopy measurements whenever the tunnel junction is not in the ballistic regime. 33 Similarly, zero-bias anomalies appearing in scanning tunneling spectra have been discussed extensively as signatures of Majorana bound states, [4][5][6]8 but may often originate from other independent causes such as bandstructure effects 34 and stacking faults. 35 Moreover, while it has been shown that Majorana bound states can indeed be realized at the end-points of linear defects in a chiral p−wave superconductor, 36 these may not exist for other types of surface defects, such as pointlike ones, or may be difficult to detect.…”
Section: Introductionmentioning
confidence: 99%